Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_at.2020.af3k.4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient bidirectional piezo-optomechanical transduction between microwave and optical frequency

Abstract: We demonstrate a lithium niobate piezo-optomechanical frequency converter which exhibits an acousto-optic modulation V π = 0.02 V and a quantum conversion efficiency of 10 − 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…In 2013, Diziain et al demonstrated second-harmonic generation in suspended 2D photonic crystals fabricated from bulk LN by FIB and wet etching of an ion-damaged buried layer [180]. On LNOI substrates, both 1D and 2D photonic crystal cavities have been demonstrated (see Figure 9(b) and (d)) [142,143,170,181,182]. With small mode volume and large local field intensity, photorefractive effects (discussed in Sec.…”
Section: Photonic Crystalmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Diziain et al demonstrated second-harmonic generation in suspended 2D photonic crystals fabricated from bulk LN by FIB and wet etching of an ion-damaged buried layer [180]. On LNOI substrates, both 1D and 2D photonic crystal cavities have been demonstrated (see Figure 9(b) and (d)) [142,143,170,181,182]. With small mode volume and large local field intensity, photorefractive effects (discussed in Sec.…”
Section: Photonic Crystalmentioning
confidence: 99%
“…As a cavity, it also allows resonant EO modulation [184], with the advantage of reduced electrode size and thus higher RC-limited operating frequency. In addition, optomechanical crystals [142,170,182] that confine both optical and mechanical modes have been demonstrated on suspended LN thin films.…”
Section: Photonic Crystalmentioning
confidence: 99%
“…The phononic, plasmonic, and OMC features are discussed by varying geometrical parameters. As shown, this design results in high VCR rate g 0 (the estimated maximum can exceed 2 × 10 6 Hz), which is predominantly contributed by moving boundary effect, in contrast to that shown in conventional designs (Jiang et al 2019(Jiang et al ,2020Shao et al 2019;Cai et al 2019). As g 0,MB and g 0,PE are out of phase, the following optimization thus focuses on the increment of g 0,MB .…”
Section: Introductionmentioning
confidence: 93%
“…As further noted that, quite different from conventional phoxonic crystal designs shown in Refs. (Jiang et al 2019(Jiang et al ,2020Shao et al 2019;Cai et al 2019), here the MB effect plays the dominant role in contributing to the overall g 0 , thus it is desirable to increase g 0,MB and suppress g 0,PE . As also demonstrated, this structure allows: a single plasmonic mode coupled to multi-phononic modes, which may find interesting application in multi-mode chip-scale OMC systems (Grutter et al 2015).…”
Section: Omc Featuresmentioning
confidence: 99%
See 1 more Smart Citation